Andrée and his balloon - Lachambre, Henri, 1846-1904.; Machuron, Alexis. (Westminster, A. Constable, 1898)
Translation of AndreÌe; au poÌ‚le Nord en ballon. Published also, New York, 1898, under title: AndreÌe's balloon expedition in search of the North pole. Mode of access: Internet.